Counteracting consumer subversion: Organizational privacy ethical care as driver of online information sharing. Issue 3 (18th August 2021) - Mattison Thompson, Frauke; Siamagka, Nikoletta‐Theofania
Abstract: With an ever‐increasing hunger for consumer data by firms, and despite many organizational efforts to reduce consumer privacy concerns, consumer subversion behavior towards information provision persists. Organizational privacy ethical care, an organizational behavior that goes beyond legislative action and moral codes, provides a new theory of how to overcome this issue. Across three studies, we develop and test theory which suggests an organizational ethic of care approach to privacy will have a positive impact on reducing consumer subversion behavior (i.e. increase consumers' willingness to share information and the accuracy of information they share). The correlational and causal results indicate that perceived organizational privacy ethical care is a positive driver of the amount and the accuracy of information consumers are willing to share with firms. The results also suggest partial support that this relationship is mediated through perceived information control and trust towards the organization. Thus, we provide some support for a better corporate approach to privacy, beyond previously suggested legislative and social responsibility standards, which allows for the reduction of consumer privacy concerns and subsequent subversion behaviors.